Intergroup struggles over victimhood in violent conflict: The victim-perpetrator paradigm - Jankowitz, Sarah (International review of victimology, 2018)
Many groups in violent, intergroup conflict perceive themselves to be the primary or sole victims of that conflict. This often results in contention over who may claim victim status and complicates a central aim of post-conflict processes, which is to acknowledge and address harms experienced by the victims. Drawing from victimology scholarship and intergroup relations theory, this article proposes the victim-perpetrator paradigm as a framework to analyse how, why and to what end groups in conflict construct and maintain their claims to the moral status of victim. This interdisciplinary paradigm builds on the knowledge that groups utilise the ‘ideal victim' construction to exemplify their own innocence and blamelessness in contrast to the wickedness of the perpetrator, setting the two categories as separate and mutually exclusive even where experiences of violence have been complex. Additionally, this construction provides for a core intergroup need to achieve positive social identity, which groups may enhance by demonstrating a maximum differentiation between the in-group as victims and those out-groups identified as perpetrators. The paradigm contributes greater knowledge on the social processes underpinning victim contention in conflict, as well as how groups legitimise their violence against out-groups during and after conflict.